The Problem of Involuntary Resettlement in Development Project - Poghosyan, Sona (Journal of Sociology: Bulletin of Yerevan University, 2013)
Nowadays various development projects aimed at generating economic growth and thereby improving general welfare are implemented in Armenia, as in many other post-Soviet countries. These large-scale infrastructural projects are usually funded by private or international donors in order to contribute to the development of various infrastructural sectors of the country, such as urban development, road construction, water supply, etc. However, internationally as well as in our country in recent years such programs may result not only in the expected positive development, but also in a number of negative social and environmental consequences such as obligatory land/property acquisition and involuntary resettlement. This is exacerbated by concerns about the possibility of long-term sustainable development approach, where economic development takes place at the expense of increasing social or environmental risks. This article discusses the problem of involuntary resettlement in development projects and analyses its characteristics in modern societies considering the Armenian experience as well.